The attack on Pearl Harbor - Bodden, Valerie (Bodden, Valerie. Disasters for all time., 2019)
Explores the events leading up to, during, and following the attack on Pearl Harbor in 1941. Includes a map, a timeline, a glossary, resources for further information, and archival photographs.